An Analysis of Differentiated Learning Strategies in the Implementation of Kurikulum Merdeka Belajar in Teaching English Writing Skills - Zahratul Fikni; Siti Ayu Surayya; Putri Hariza Sholihah; Muhammad Husnu (UIBU, 2024)
The present study aimed to disclose the state of English writing proficiency among students and analyze how differentiated learning strategies in Kurikulum Merdeka Belajar approaches address the needs of different student populations when teaching writing English. This study used descriptive qualitative methods which employed observation, questionnaire and interview to collect the data. The participants of this study were one English subject teacher and 35 grade XK of students of MA. Muallimat NWDI Pancor in the academic year 2023-2024. The study's findings demonstrated that, while students' writing is currently in fairly good condition, it is far from perfect, as shown by the percentage data presented. The occasionally answer had the highest percentage data presentation, totaling 42.86%. There were 24 students who thought that they had difficulty to found an interesting idea to write about. Differentiated learning strategies can meet the needs of divers students in teaching writing English throuhg deviding students based on learning styles, namely visual, auditory and kinesthetic. It supports the quality of students' English writing learning, especially in finding interesting topics to write about because this learning provides suitability of materials, processes and tasks or projects according to the needs, abilities and creativity of students in the learning process.